Smooth muscle hamartoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
An 11-month-old boy was first observed due to a hard tumefaction of the left foot and leg, which was noted by his parents at the age of 4 months. On physical examination, there was hypertrichosis of the lower third of his left leg and a tumefaction of the dorsal surface of his left foot, which was more evident on the big toe, and of the front surface of the lower third of the left leg (Fig. 1). At palpation, there was a tumefaction with blurred outlines, hard-fibrous in consistency and not painful. The movement of flexion of the foot on the leg was limited and showed deep transverse furrows, level with which the neoformation was less thick. A fibrous proliferation was clinically hypothesized. However, the histological examination (Fig. 2 and box) showed a proliferation of smooth muscle cells without atypia, leading to the final diagnosis of smooth muscle hamartoma and suggesting a period of clinical observation.